Are emerging farmers the missing link for mechanised Conservation agriculture? Viewpoints from Zambia. Issue 3 (3rd April 2022) - Omulo, Godfrey; Daum, Thomas; Köller, Karlheinz; Birner, Regina
ABSTRACT: Conservation agriculture's (CA) potential to improve resilience to climate change, environmental degradation, and food insecurity across Africa is hampered by critical challenges, especially high labour requirements without mechanisation. Yet, whether medium-scale farmers owning 5–100 hectares of farmland and tractors can be the antidote for CA upscaling remains unclear. Based on insights from Zambia, the authors argue that medium-scale farmers can contribute to CA upscaling since they cultivate large farms and rent tractors to smallholder farmers. Harnessing the synergies between CA, mechanisation, and medium-scale farmers requires research on how they perceive CA, the enabling environment for mechanised CA, and appropriate policies.